THE EFFECT OF MARKETING MIX STRATEGY ON MARKETING PERFORMANCE OF SMALLHOLDER RUBBER FARMERS IN GUNUNG TOAR DISTRICT, KUANTAN SINGINGI REGENCY - Bella Fadila; Shorea Khaswarina; Yeni Kusumawaty (Agricultural Socio-Economics Journal, 2022)
The development of the plantation sub-sector with a marketing mix strategy approach is a comprehensive and sustainable solution for the development of human and economic resources in rural areas. Marketing performance is used to determine the level of marketing success. The purpose of this study was to analyze the effect of marketing mix strategy consisting of differentiation of agricultural products, functionalization of elasticity of agricultural products, added value and resonance on the marketing performance of smallholder rubber farmers in Gunung Toar District, Kuantan Singingi Regency. The population in this study were smallholder rubber farmers with a sample of 34 farmers who were determined by the simple random sampling method. The data analysis method used is multiple linear regression using SPSS software. The results showed that the marketing mix strategy consisting of agricultural product differentiation (X1) and agricultural product elasticity functionalization (X2) had a significant effect, and added value (X3) and resonance (X4) had no significant effect on marketing performance. smallholder rubber farmers in Kab. Mount Toar, Kuantan Singingi Regency.